2018
DOI: 10.1080/08923973.2017.1418882
|View full text |Cite
|
Sign up to set email alerts
|

The β2-adrenoceptor agonist clenbuterol reduces the neuroinflammatory response, neutrophil infiltration and apoptosis following intra-striatal IL-1β administration to rats

Abstract: The results provide evidence that clenbuterol elicits anti-inflammatory effects, suppresses the peripheral acute phase response and reduces the infiltration of neutrophils and apoptotic response to acute IL-1β-induced brain injury. Suppression of both the central and peripheral response following clenbuterol administration may contribute to its protective properties following brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Inflammatory cytokines are now considered as important pro-apoptotic factors involved in the progression of neurological disorders (59). For example, intra-striatal IL-1β administration in rats, which triggers inflammatory responses, is subsequently accompanied with increased apoptosis 24 h post-injection, an effect which then promotes brain injury (60). In the present study, we found that the depression-like symptoms observed in rats following chronic stress were accompanied by a marked increasing in neuronal apoptosis within vmPFC regions.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines are now considered as important pro-apoptotic factors involved in the progression of neurological disorders (59). For example, intra-striatal IL-1β administration in rats, which triggers inflammatory responses, is subsequently accompanied with increased apoptosis 24 h post-injection, an effect which then promotes brain injury (60). In the present study, we found that the depression-like symptoms observed in rats following chronic stress were accompanied by a marked increasing in neuronal apoptosis within vmPFC regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our most recent data support this potential hypothesis [9]. Additionally, neutrophils are the innate immune response and thus, neutrophilic infiltration of tissues is involved in many inflammatory diseases [18,19]. In order to inhibit the neutrophilic infiltration from tissue injury (I/R injury, brain injury, ethanol feeding-induced liver injury), several inhibitors such as MgIG (Magnesium isoglycyrrhizinate), Clenbuterol, Phillyrin, or PAI-1 (Plasminogen activator inhibitor-1) have been widely studied [20,21].…”
Section: Discussionsupporting
confidence: 68%
“…Since we were attempting to restore the activities of epinephrine and corticosterone at the basal levels that were completely depleted by AD procedure and provide the additional replenishment for increased levels observed during ozone exposure in SH rats, these relatively high doses were selected. Although these doses are several fold higher than those used therapeutically, these CLEN and DEX concentrations are within the range used in other laboratory rodent studies for the purpose of inducing bronchodilation and immunosuppression, respectively (Griffin et al, 2018;Jonasson et al, 2013).…”
Section: Methodsmentioning
confidence: 85%